The impact of presence of Hashimoto's thyroiditis on diagnostic accuracy of ultrasound‐guided fine‐needle aspiration biopsy in subcentimeter thyroid nodules: A retrospective study from FUSCC. (5th April 2017) - Gao, Lili; Ma, Ben; Zhou, Li; Wang, Yu; Yang, Shuwen; Qu, Ning; Gao, Yi; Ji, Qinghai
Abstract: The incidence of PTMC has been increasing in the recent years. This study aimed to investigate the diagnostic value of US‐FNA in thyroid nodules ≤1 cm and whether the presence of Hashimoto's thyroiditis (HT) in thyroid could influence the accuracy. The patients who accepted US‐FNA at FUSCC from December 2012 to November 2015 and followed our criteria were enrolled in this study. We extracted the cytological, pathological, and follow‐up US/US‐FNA data of patients with subcentimeter nodules. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), false‐negative rate (FNR), false‐positive rate (FPR), and AUC were calculated to define FNA diagnostic performance in patients. The association of HT with cytological results was analyzed in univariate and multivariate logistic regression analysis. In total, 754 patients with 817 subcentimeter nodules were collected to comprise the FUSCC cohort. Of the 817 nodules, the cytological results were ND/UNS in 80 nodules (9.8%), benign in 74 (9.1%), AUS/FLUS in 80 (9.8%), FN/SFN in 6 (0.7%), suspicious for malignancy (SM) in 222 (27.2%), and malignant in 355 (43.5%). The sensitivity, specificity, PPV, NPV, and AUC of US‐FNA for the subcentimeter nodules were 98.8%, 90.5%, 98.8%, 90.5%, and 94.7%, respectively. In comparison with HT‐positive subcentimeter nodules, the diagnostic value of US‐FNA for HT‐negative nodules was significantly higher (HT‐positive: AUC = 91.6%, HT‐negative: AUC = 95.9%, P  =   0.028). The coexistent HT was found to increase the risk of the FNR and indeterminate cytological results. US‐FNA demonstrated an effective method for diagnosis of subcentimeter thyroid nodules with a low nondiagnostic rate in our study. The presence of HT in thyroid could be a risk factor for the increased FNR and indeterminate cytological results during US‐FNA. Abstract : The incidence of PTMC has been increasing in the recent years. This study aimed to investigate the diagnostic value of US‐FNA in thyroid nodules ≤1 cm and whether the presence of Hashimoto's thyroiditis (HT) in thyroid could influence the accuracy.